Role of the gldK gene in the virulence of Riemerella anatipestifer. (25th January 2019) - Yuan, Hui; Huang, Li; Wang, Mingshu; Jia, Renyong; Chen, Shun; Liu, Mafeng; Zhao, Xinxin; Yang, Qiao; Wu, Ying; Zhang, Shaqiu; Liu, Yunya; Zhang, Ling; et al.
ABSTRACT: Riemerella anatipestifer ( R. anatipestifer ) is a major bacterial pathogen that causes pericarditis, perihepatitis, and airsacculitis in ducks. However, the pathogenesis of R. anatipestifer is still unclear. Type IX secretion system (T9SS ) has been reported to be related to the pathogenic properties of the phylum Bacteroidetes, gldK gene was a major component of this secretion. In this study, we used a homologous recombination method to construct a gldK mutant strain, and found that the survival rate of gldK mutant strain infected ducks was 80%, while R. anatipestifer CH-1 wild-type-infected ducks was only 20%, the median lethal dose (LD50 ) of the gldK mutant strain was 2.25 × 10 11, which is approximately 1.5 × 10 3 -fold higher than that of the wild-type strain (1.44 × 10 8 ). The bacterial loads in the blood, liver, and brain tissues of gldK mutant strain-infected ducks were also considerably lower than those of R. anatipestifer CH-1 wild-type-infected ducks. In conclusion, gldK gene can be deleted, suggesting that the gldK gene was a non-essential gene for growth. However, it plays an important role in the bacterial virulence of R. anatipestifer CH-1.